Physical activity level among children recovering from severe acute malnutrition. Issue 2 (4th January 2018) - Babirekere‐Iriso, Esther; Rytter, Maren Johanne Heilskov; Namusoke, Hanifa; Mupere, Ezekiel; Michaelsen, Kim F.; Stark, Ken D.; Lauritzen, Lotte; Briend, André; Friis, Henrik; Brage, Søren; Faurholt‐Jepsen, Daniel
Abstract: Objective: To assess the level and predictors of physical activity at discharge among children recovering from severe acute malnutrition (SAM). Methods: We conducted a prospective study among 69 children 6–59 months of age admitted with SAM for nutritional rehabilitation at Mulago National Referral Hospital, Uganda. Using hip‐mounted triaxial accelerometers, we measured physical activity expressed as counts per minute (cpm) during the last three days of hospital treatment. As potential predictors, we assessed clinical and background characteristics, duration to transition phase and duration of hospitalisation, serum C‐reactive protein and whole‐blood docosahexaenoic acid (DHA). Multiple linear regression analyses were used to identify predictors of physical activity. Results: The median (IQR) age was 15.5 (12.6; 20.5) months. At discharge, the mean (SD) movement was 285 (126) cpm. Physical activity was 43 (19; 67) cpm higher for each unit increase in weight‐for‐height z‐score (WHZ) and 72 (36; 108) cpm higher for each centimetre increase in MUAC. Whole‐blood DHA on admission was also a positive predictor of physical activity, whereas duration to transition phase and duration of hospitalisation were both negative predictors. Conclusion: The level of physical activity at discharge among children treated for SAM was low. WHZ, MUAC and DHA on admission were positive predictors of physical activity, whereas duration of stabilisation and hospitalisation was negative predictors of physical activity. These results suggest that assessment of physical activity may be used as a marker of recovery.